Determination of total folate content in traditional foods from Black Sea Area countries - Finglas, P. (2012)
Rationale and objectives: Folates occur naturally as a variety of polyglutamates, with different biological activity. Folate is a generic term for a water-stable vitamin from B-complex, which exists in many chemical forms. It is essential for many of the methylation reactions involved in the synthesis of DNA and RNA, and hence plays a crucial role in cell division. The recommended daily allowance (RDA) is 400 µg/day (for both men and women) of dietary folate equivalents. Food folates have approximately 50% lower bioavailability than folic acid. The ingestion of a supplement of folic acid during the periconceptional period significantly reduces the risk of giving birth to a child with a neural tube defect. Materials and methods: The determination of the total folate content in foodstuffs was carried out by a microbiological assay (EN 14131:2003) with turbidimetric detection of the growth of the microorganism Lactobacillus casei, subspecies rhamnosus (ATCC 7469). The analyses were performed in an accredited laboratory according to ISO/IEC/17025. This method was applied to the selected traditional foods of European Project BaSeFood (Sustainable Exploitation of Bioactive Components from the Black Sea Area Traditional Foods). Results: Total folate content of cereals or cereals based foods ranged from 11.7 to 20.5 µg/100 g, while for vegetables based foods it varied between 5.2 µg/100 g (Ukrainian Borsch) and 97.2 µg/100 g (Nettles with walnut sauce). The highest total folate content was found in the group of products from oilseeds for roasted sunflower seeds (113 µg/100 g). All traditional foods containing fruits have a total folate content lower than 5 µg/100 g. The analytical results are expressed per 100 g of edible portion. Conclusions: Our results show that some of the analysed traditional foods are a good dietary source of natural folates in the diet of Black Sea Area countries. Fruit based foods presented the lower total folate content and products from oilseeds were the group with the highest content.